The concept of saving dental health among learners in the Russian Federation - M. K. Makeeva; E. L. Kovrizhkina; G. A. Oks; S. A. Fokina; T. A. Mityushkina; M. V. Kostinskaya; A. V. Shegai (Эндодонтия Today)
AIM. To analyse the current literature data on the topic of the concept of saving dental health of students in the Russian Federation.MATERIALS AND METHODS. Russian and foreign topical publications in electronic databases: Elibrary, Cyberleninka, GoogleScholar were analysed. The articles, the content of which refers to the concept of saving dental health of students in the Russian Federation, were selected and included in the review.RESULTS. A total of 247 articles were reviewed. After analysing the literature according to the inclusion criteria, the ﬁnal number was 83. The articles were selected and included in the review, the content of which is related to the concept of saving dental health among students of the Russian Federation.CONCLUSIONS. The high prevalence of dental diseases among the younger generation indicates the need for wider implementation of preventive measures and introduction of preventive programmes.